Influence of information provided prior to switching from Humira to biosimilar adalimumab on UK patients’ satisfaction: a cross-sectional survey by patient organisations - Kaneko, K; Prieto Alhambra, D; Jacklin, C; Bosworth, A; Dickinson, S; Berry, S; McAteer, H; Taylor, PC (BMJ Publishing Group, 2022)
Objectives To investigate the perceptions and experiences of people with specific immune-mediated inflammatory diseases during the process of switching from Humira to biosimilar adalimumab. Design Cross-sectional survey. Setting An anonymised, self-administered, web-based survey. Participants The participants were drawn from members and non-members of either the National Rheumatoid Arthritis Society, the National Axial Spondyloarthritis Society, Crohn’s and Colitis UK, or Psoriasis Association. Birdshot Uveitis Society and Olivia’s Vision also signposted to the survey links. Results A total of 899 people living with various immune mediated inflammatory diseases participated in this survey. Thirty-four per cent of respondents reported poor overall satisfaction with their biosimilar adalimumab after the switch, associated with complaints related to the switching process including lack of shared decision making, scarcity of information provided by or signposted to by the department instigating the switch as well as lack of training with the new injection device. Where training with the new device had been provided, there were significantly reduced reports of pain when injecting the new biosimilar (OR 0.20, 95% CI 0.07 to 0.55), side effects (OR 0.17, 95% CI 0.06 to 0.47) and difficulty in using the new injection device (OR 0.25, 95% CI 0.15 to 0.41). Self-reported side effects were reduced by (OR 0.13, 95% CI 0.05 to 0.38) when written information was provided by healthcare professionals and by (OR 0.15, 95% CI 0.05 to 0.42) with provision of verbal information. Difficulty in using the new injection device was also reduced by provision of satisfactory information such as written documents (OR 0.38, 95% CI 0.23 to 0.63) or by verbal communication with healthcare professionals (OR 0.45, 95% CI 0.27 to 0.73). Finally, provision of satisfactory written or verbal information was associated with a reduction in any negative perception regarding symptom control with the new biosimilar by (OR 0.05, 95% CI 0.004 to 0.57) and by (OR 0.15, 95% CI 0.03 to 0.84), respectively. Conclusions Patient reported experiences of the process of switching from originator to biosimilar emphasise the importance of clear communication, training and information in order to optimise perception and maximise achievable outcomes with the new treatment.